2022
DOI: 10.3390/cancers14163859
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Prediction Model for Overall Survival after Stereotactic Body Radiation Therapy for Primary Non-Small Cell Lung Cancer Using Radiomics Analysis

Abstract: Stereotactic body radiation therapy (SBRT) for early-stage non-small cell lung cancer (NSCLC) leads to recurrence in approximately 18% of patients. We aimed to extract the radiomic features, with which we predicted clinical outcomes and to establish predictive models. Patients with primary non-metastatic NSCLC who were treated with SBRT between 2002 and 2022 were retrospectively reviewed. The 358 primary tumors were randomly divided into a training cohort of 250 tumors and a validation cohort of 108 tumors. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Franceschini et al successfully predicted disease-specific survival in patients treated with SBRT using four radiomic features (Franceschini et al 2020 ). Sawayanagi et al developed an OS prediction model for primary NSCLC after SBRT through radiomics analysis (Sawayanagi et al 2022 ). Jiao et al also developed a radiomic model to integrate risk of death estimates based on pre- and post-treatment CT scans in patients receiving SBRT (Jiao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Franceschini et al successfully predicted disease-specific survival in patients treated with SBRT using four radiomic features (Franceschini et al 2020 ). Sawayanagi et al developed an OS prediction model for primary NSCLC after SBRT through radiomics analysis (Sawayanagi et al 2022 ). Jiao et al also developed a radiomic model to integrate risk of death estimates based on pre- and post-treatment CT scans in patients receiving SBRT (Jiao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics, a non-invasive technology that converts medical images into a high-dimensional mineable feature space via high-throughput quantitative feature extraction (Bera et al 2022 ; Gillies et al 2016 ; Lambin et al 2012 , 2017 ; Reuze et al 2018 ), has been introduced for the prediction of treatment responses, patient stratification, and prognosis for lung cancer patients in recent years (Chen et al 2017 , 2023 ; Constanzo et al 2017 ; Coroller et al 2015 ; Huang et al 2016 ; Lee et al 2017 ; Li et al 2018 ; Mattonen et al 2016 ). In particular, radiomic features extracted from CT images have shown promising performance in predicting OS in NSCLC patients treated with SBRT (Jiao et al 2021 ; Li et al 2018 ; Sawayanagi et al 2022 ; Somasundaram et al 2023 ; Starkov et al 2019 ). However, most studies to date have employed OS as endpoint and there is a scarcity of studies that have integrated clinical and radiomic features to predict cancer-specific survival (CSS) in lung cancer patients undergoing SBRT.…”
Section: Introductionmentioning
confidence: 99%
“…These potential biases may have an impact on the validity and reproducibility of the model. In another study, Sawayanagi et al demonstrated the prognostic value of GTV-derived GLSZM features on the pretherapy CT image on OS in patients with localized NSCLC treated with curative SBRT [39]. In contrast to these studies, the present study was designed with a much larger sample size and, more importantly, with external testing sets treated by SBRT.…”
mentioning
confidence: 94%
“…These radiomic features, obtained prior to treatment initiation, offer invaluable insights into treatment outcomes and the likelihood of adverse events. Sawayanagi et al 6 investigated SBRT for early-stage NSCLC, identifying a radiomic feature and predictive model for overall survival, as well as assessing recurrence rates. Shen et al 7 established a predictive model employing radiomic features for radiation-induced liver disease in patients with hepatocellular carcinoma undergoing SBRT.…”
mentioning
confidence: 99%